Pressure-induced stacking disorder in boehmite. Issue 24 (6th June 2018) - Ishii, Y.; Komatsu, K.; Nakano, S.; Machida, S.; Hattori, T.; Sano-Furukawa, A.; Kagi, H.
Abstract : The structure of an aluminum layered hydroxide, boehmite (γ-AlOOH), as a function of pressure was studied by using in situ synchrotron X-ray and neutron diffraction. Abstract : The structure of an aluminum layered hydroxide, boehmite (γ-AlOOH), as a function of pressure was studied by using in situ synchrotron X-ray and neutron diffraction. Peak broadening, which is only found for hkl ( h ≠ 0) peaks in the X-ray diffraction patterns, is explained by stacking disorder accompanying a continuously increasing displacement of the AlO6 octahedral layer along the a -axis. This finding could be the first experimental result for pressure-induced stacking disorder driven by continuous layer displacement. The magnitude of the layer displacement was estimated from the X-ray scattering profile calculation based on the stacking disordered structure model. Hydrogen bond geometries of boehmite, obtained by structure refinements of the observed neutron diffraction patterns for the deuterated sample up to 10 GPa, show linearly approaching O–D covalent and D⋯O hydrogen bond distances and they merge below 26 GPa. Pressure-induced stacking disorder makes the electrostatic potential of hydrogen bonds asymmetric, yielding less chance for proton-tunnelling.